Sustainable Agriculture Research 2000–2026 Core Themes Growth Trajectories and Knowledge Networks: A Bibliometric Review - Judijanto, Loso (West Science Nature and Technology, 2026)
This study aims to map the intellectual structure, thematic evolution, and collaboration patterns of sustainable agriculture research from 2000 to 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to identify core themes, research trajectories, and knowledge networks. The results indicate a significant growth in publications, particularly after 2015, reflecting increasing global attention to sustainability challenges in agriculture. Co-occurrence analysis reveals several dominant thematic clusters, including environmental sustainability, soil and nutrient management, technological innovation (e.g., precision agriculture and machine learning), and biological aspects of crop production. Density visualization highlights that while core topics such as sustainable agriculture and resource management are well-established, emerging areas such as circular economy, carbon management, and AI-driven agriculture remain relatively underexplored. In addition, collaboration network analysis suggests that research is largely dominated by developed countries, although contributions from developing regions are gradually increasing. This study contributes by providing a comprehensive overview of research trends and identifying future research directions to support the development of sustainable and resilient agricultural systems.